The ant genus Strumigenys Smith, 1860 (Hymenoptera: Formicidae) in western North America North of Mexico - Booher, Douglas B. (Zootaxa, 2021)
Strumigenys is a globally distributed genus of mostly cryptic leaf-litter ants. In North America they are common throughout eastern deciduous forests but become increasingly rare to the west. Here I review the Strumigenys fauna of western North America north of the Mexico border including all states west of the eastern border of Texas. Six new native species with ranges entirely within this region are described: S. collinsae sp. nov., S. macgowni sp. nov., S. mendezi sp. nov., S. moreauviae sp. nov., S. lucky sp. nov., and S. subtilis sp. nov. Strumigenys ananeotes Longino & Booher 2019 is given a more thorough description, and S. alberti Forel 1893, a Neotropical species, is reported from the region for the first time. All new species bear clear morphological relationships with a native North American clade of “smithistrumiform” species. I include species accounts and provide an illustrated key for all species of this region.